exam1problemsetsolutions-1

# exam1problemsetsolutions-1 - Topic 3 Null Space Q6 A= 10 0...

This preview shows pages 1–19. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Topic 3: Null Space. Q6: A= 10 0 12 16 we want Ax = 0, x = (x1 , x2 , x3 )T , which is just x1 10 1 2 x2 = 0 016 x3 Thus, we have 10x1 + x2 + 2x3 = 0, (1) x2 + 6x3 = 0, (2) Look at the second equation, we get x2 = −6x3 Plug it into the ﬁrst equation, we get 10x1 − 4x3 = 0 Therefore, x1 and x3 are dependent, I could now pick x1 = 1, then x3 = 5/2, again use x2 = −6x3 we get x3 = −15, thus the null space of A could be spanned by x = (1, −15, 5/2)T , in other words, x = (1, −15, 5/2)T is a basis of the null space. Notice rank (A) = 2, the x has 3 variables, so the dimension of your null space is 3 − 2 = 1, which coincides with the answer. 1 Q7: A= 10 0 123 168 x1 x2 x3 = 0 x4 we want Ax = 0, x = (x1 , x2 , x3 , x4 )T , which is just 10 1 2 3 0 1 6 −8 Thus, we have Look at the second equation, we get 10x1 + x2 + 2x3 + 3x4 = 0, (1) x2 + 6x3 − 8x4 = 0, (2) x2 = −6x3 + 8x4 Plug it into the ﬁrst equation, we get 10x1 − 4x3 + 11x4 = 0 Now x1 , x3 and x4 are dependent, we can choose any values for two of them to determine the third one. Here, I will choose x1 = 1, x3 = 0 ﬁrst, then x4 = −10/11, again use x2 = −6x3 + 8x4 we get x2 = −80/11, so x(1) = (1, −80/11, 0, −10/11)T . We are not done yet, remember rank (A) = 2, and the x has 4 variables, so the dimension of the null space should be 4 − 2 = 2, so you still need one more vector. OK, now I choose x1 = 0, x3 = 1, then x4 = 4/11, again use x2 = −6x3 + 8x4 we get x2 = −34/11, so x(2) = (0, −34/11, 1, 4/11)T . Now we are done. The null space of A could be spanned by x(1) and x(2) , in other words, x(1) and x(2) is the basis of the A’s null space. 2 ...
View Full Document

{[ snackBarMessage ]}

### Page1 / 19

exam1problemsetsolutions-1 - Topic 3 Null Space Q6 A= 10 0...

This preview shows document pages 1 - 19. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online